Non-Coding RNAs Participate in the Pathogenesis of Neuroblastoma - Rezaei, Omidvar; Honarmand Tamizkar, Kasra; Hajiesmaeili, Mohammadreza; Taheri, Mohammad; Ghafouri-Fard, Soudeh (Frontiers in Oncology, 2021)
Neuroblastoma is one of the utmost frequent neoplasms during the first year of life. This pediatric cancer is believed to be originated during the embryonic life from the neural crest cells. Previous studies have detected several types of chromosomal aberrations in this tumor. More recent studies have emphasized on expression profiling of neuroblastoma samples to identify the dysregulated genes in this type of cancer. Non-coding RNAs are among the mostly dysregulated genes in this type of cancer. Such dysregulation has been associated with a number of chromosomal aberrations that are frequently detected in neuroblastoma. In this study, we explain the role of non-coding transcripts in the malignant transformation in neuroblastoma and their role as biomarkers for this pediatric cancer.